The Influence of Environmental Performance, Company Size, and Independent Commissioners on Carbon Emission Disclosure - Kania Salsabila (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2023)
Global warming caused by the increase in carbon emissions is the impact of the company's operational activities that use machines with large capacities. The study aims to empirically prove the influence of environmental performance, firm size and independent board of commissioners on carbon emission disclosure. The population in the study were 165 companies in the energy sector and basic materials sector companies listed on the Indonesian Stock Exchange during the study period (2018-2021). Determination in this sample used purposive sampling and based on existing criteria obtained as many as 29 companies with a total of 116 data observation. Data analysis techniques use panel data regression with EViews software version 9. The results of the study show that simultaneously environmental performance, firm size and independent board of commissioners have a significant impact on carbon emission disclosure. Partially variable environmental performance and firm size have a significant influence on carbon emission disclosure. Independent board of commissioners partially had no significant influence on carbon emission disclosure.